2009
DOI: 10.3945/jn.108.101865
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Product Intake Modifies the Association between Interleukin-10 Genetic Polymorphisms and Gastric Cancer Risk

Abstract: In this study, our aim was to investigate the association of inflammation-related genetic polymorphisms and gastric cancer risk and to examine whether the combined effect of soybean product intake modified cancer risk. Eighty-four incident gastric cancer cases and 336 matched controls were selected from the Korean Multi-Center Cancer Cohort. We selected 14 single nucleotide polymorphisms (SNP) from 5 genes [interleukin (IL)-1beta, IL-2, IL-4, IL-8, and IL-10] and used unconditional logistic regression model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…After reading the full texts of the remaining 37 articles, we found one article had not sufficient data of genotype for calculating OR and 95% CI, four articles were meta-analyses, and two articles were reviews. Finally, a total of 30 studies (4)(5)(6)(7)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) published from 2002 and 2015 with 6,101 cases and 8,557 controls met our inclusion criteria. The main characteristics of these studies were listed in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full texts of the remaining 37 articles, we found one article had not sufficient data of genotype for calculating OR and 95% CI, four articles were meta-analyses, and two articles were reviews. Finally, a total of 30 studies (4)(5)(6)(7)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) published from 2002 and 2015 with 6,101 cases and 8,557 controls met our inclusion criteria. The main characteristics of these studies were listed in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that capsaicin consumption, H. pylori infection, and IL-1B-31C genotypes may affect gastric carcinogenesis via the same metabolic pathway (e.g., an increased inflammatory response and an altered gastric acidic environment). In South Korea, Ko et al [49] investigated several inflammation-related polymorphisms and found that IL-10 genetic variants and low intake of soybean products increased gastric cancer risk compared with the same variants combined with high consumption of soybean products. Soybeans are a major source of isoflavones (e.g., genisten and daidzein), which have anti-inflammatory and anti-oxidative effects.…”
Section: Effect Of Carcinogen Metabolism-related Genetic Polymorphismmentioning
confidence: 99%
“…Soybeans are a major source of isoflavones (e.g., genisten and daidzein), which have anti-inflammatory and anti-oxidative effects. In those who consume fewer soybeans, IL-10 genetic variants may allow infection with more virulent H. pylori strains and increase gastric inflammation [49] . Oliveira et al [50] investigated the modifying effects of alcohol on the association between genetic polymorphisms anti-or pro-inflammatory cytokines and gastric cancer risk in Southeast Brazilians but found no significant interactions.…”
Section: Effect Of Carcinogen Metabolism-related Genetic Polymorphismmentioning
confidence: 99%
“…Twenty-two studies (Wu et al, 2002;Wu et al, 2003 Morgan et al, 2006;García-González et al, 2007;Sugimoto et al, 2007;Bai et al, 2008;Crusius et al, 2008;Deng et al, 2008;Zhou et al, 2008a;Kang et al, 2009;Ko et al, 2009;Xiao et al, 2009;Liu et al, 2011;Zhou et al, 2011) were initially included in our meta-analysis. Those 22 studies were preliminarily appropriate to the meta-analysis of the associations with gastric cancer regarding IL-10-1082 A/G SNP.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Since the year 2002, a lot of studies have focused on the IL-10-1082 G allele association with the susceptibility to gastric cancer, but with mixed or conflicting results (Wu et al, 2002;El-Omar et al, 2003;Wu et al, 2003;Savage et al, 2004;Alpízar-Alpízar et al, 2005;Guo et al, 2005;Lee et al, 2005;Lu et al, 2005;Zambon et al, 2005;Kamangar et al, 2006;Morgan et al, 2006;García-González et al, 2007;Sugimoto et al, 2007;Bai et al, 2008;Crusius et al, 2008;Deng et al, 2008;Zhou, et al, 2008a;Kang et al, 2009;Ko et al, 2009;Xiao et al, 2009;Liu et al, 2011;Zhou et al, 2011). Up to now, there has been just one relevant published meta-analysis regarding IL-10-1082 A/G SNP (Zhou et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%